Does the Environment Impact Entrepreneurial Business Intention? - Wishnu Wardana, Ludi; Mukhtar, Saparuddin; Wibowo, Agus; Shandy Narmaditya, Bagus; Eka Suprajan, Sandy; Subali Patma, Tundung; Martha Mahendra, Angga (KnE Social Sciences, 2021)
This study aims to investigate the determinants that influence youth in preparing for entrepreneurship in Indonesia. A quantitative approach was applied, using a cross-sectional survey with 425 young entrepreneur respondents in East Java. Data were analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS). The findings showed that entrepreneurial intentions can be explained by the institutional environment and can provide motivation to start a business. This study confirmed the strong correlation between motivation to start a business and entrepreneurial intentions in preparing for entrepreneurship programs. Keywords: Institutional Environment, Motivate to Start a Business, Entrepreneurial Intentions